Risk Factors and Predictive Score Model for Early Recurrence After Curative Surgery in Patients With Poorly Differentiated Gastrointestinal Neuroendocrine Neoplasms - Li, Chengguo; Zhang, Peng; Sun, Xiong; Tong, Xin; Chen, Xin; Li, Chong; Yang, Wenchang; Liu, Weizhen; Wang, Zheng; Tao, Kaixiong (Frontiers in Surgery, 2021)
Purpose Studies on early recurrence in gastrointestinal neuroendocrine carcinoma (NEC) and mixed adenoneuroendocrine carcinoma (MANEC) are lacking and risk factors related to early recurrence are not clear. We evaluated risk factors for early recurrence in such patients and developed a predictive scoring model. Methods Patients undergoing curative surgery for GI-NEC or MANEC between January 2010 and January 2019 were included. Early recurrence was defined as recurrence within 12 months after surgery. Risk factors for early recurrence were identified using logistic regression. Results Of the 86 included patients, 30 developed early recurrence and 56 had no early recurrence. Independent risk factors associated with early recurrence included tumor location in the midgut/hindgut (odds ratio (OR)=3.941, 95% confidence interval (CI) 1.067-14.565, p=0.040), alkaline phosphatase (ALP) >81 (OR=4.848, 95% CI 1.600-14.688, p=0.005), and lymph node ratio (LNR) >0.18 (OR=4.761, 95% CI 1.640-13.818, p=0.004). Risk scores were assigned to tumor location (foregut, 0; midgut/hindgut, 1), ALP (≤81, 0; >81, 1), and LNR (≤0.18, 0; >0.18, 1). Patients with a high risk (score 2-3) for early recurrence had significantly shorter disease-free survival and overall survival than those with low- (score 0) and intermediate risks (score 1) (both p<0.001). The novel scoring model had superior predictive efficiency for early recurrence over TNM staging (area under the curve 0.785 vs. 0.610, p=0.002). Conclusion Tumor location, preoperative ALP, and LNR were independent factors associated with early recurrence after curative surgery for GI-NEC or MANEC. The risk scoring model developed based on these three factors shows superior predictive efficiency.